A definite measure of occupancy exposures, seeking with non-radiolabeled in vivo 5-HT2A receptor occupancy and in vitro free fractions. (4th July 2018) - Bhyrapuneni, Gopinadh; Thentu, Jagadeesh Babu; Palacharla, Veera Raghava Choudary; Muddana, Nageswararao; Aleti, Raghupathi Reddy; Ajjala, Devender Reddy; Nirogi, Ramakrishna
Abstract: Unbound drug concentration in the brain would be the true exposure responsible for specific target occupancy. Drug exposures from preclinical are total concentrations of those over/underestimate the clinical dose projection. With the application of mass spectrometry, the current work proposes a definite measure of test drug exposures at serotonin-2A occupancy. The 5-HT2A occupancy of antagonist in the rat brain has determined with non-radiolabeled tracer MDL-100, 907 at an optimized dose (3 µg/kg) and treatment time (30 min). Equilibrium dialysis method determines the in vitro free fraction of the test antagonist in untreated rat brain homogenates and plasma. Drug-free fractions derived the unbound concentration (EC50 ) in plasma and brain at test doses. The corresponding binding affinities (Ki) correlated with the unbound concentrations. Except for quetiapine, the ED50 values in the dose-occupancy curves of antagonists are close and ranged from 1 to 3 mg/kg. The test drug quetiapine, eplivanserin, and clozapine showed high free fractions in plasma, but for ketanserin and olanzapine, the brain free fraction was higher. The correlation between the unbound EC50 of the antagonists and corresponding Ki values was good ( r 2 =0.828). The improved EC50 accuracy with unbound concentrations was 10–250 folds in plasma and 10–170 folds in the brain. Further, the free fractions ( f u, plasma / f u, brain ) of test drugs had shown a correlation of ∼83% with brain permeability ( C total brain / C total plasma ), a limiting factor. Thus, correlating the occupancy with unbound exposure and pharmacology would result in an accurate measurement of drug potency and optimizes in selecting the clinical dose.